PRIVILEGED COMMUNICATION AND THE COUNSELLOR - LeBlanc, Paul (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1972)
A serious dilernma faces the professional who is called upon as a witness to make publie, in a court of law, facts which have been revealed to him in the strictest confidence. On the one hand lies his duty to give the court aIl the information at his disposal so that justice can be done; on the other, there is his implied, or even explicit, undertaking to refrain from divulging communications confidentially made for the purpose of obtaining advice or assistance.